The Vietnam War. Volume one (episodes 1-5) [videorecording (DVD)] - Ward, Geoffrey C.; Reznor, Trent; Ross, Atticus, 1968- (PBS Distribution, 2017)
In an immersive narrative, Burns and Novick tell the epic story of the Vietnam War as it has never before been told on film. Features testimony from nearly 100 witnesses, including many Americans who fought in the war and others who opposed it, as well as Vietnamese combatants and civilians from both the winning and losing sides.